Effect of osmotic stress on potassium accumulation around glial cells and extracellular space volume in rat spinal cord slices - Vargová, L; Chvátal, A; Anderová, M; Kubinová, S; Ziak, D; Syková, E (Journal of neuroscience research, 2001)
In rat brain and spinal cord slices, the local extracellular accumulation of K(+), as indicated by K(+) tail currents (I(tail)) after a depolarization step, is greater in the vicinity of oligodendrocytes than that of astrocytes. It has been suggested that this may reflect a smaller extracellular space (ECS) around oligodendrocytes compared to astrocytes [Chvátal et al. [1997] J. Neurosci. Res. 49:98-106; [1999] J. Neurosci. Res. 56:493-505). We therefore compared the effect of osmotic stress in spinal cord slices from 5-11-day-old rats on the changes in reversal potentials (V(rev)) of I(tail) measured by the whole-cell patch-clamp technique and the changes in ECS volume measured by the real-time iontophoretic method. Cell swelling induced by a 20 min perfusion of hypoosmotic solution (200 mmol/kg) decreased the ECS volume fraction from 0.21 +/- 0.01 to 0.15 +/- 0.02, i.e., by 29%. As calculated from V(rev) of I(tail) using the Nernst equation, a depolarizing prepulse increased [K(+)](e) around astrocytes from 11.0 to 44.7 mM, i.e., by 306%, and around oligodendrocytes from 26.1 to 54.9 mM, i.e., by 110%. The ECS volume fraction decrease had the same time course as the changes in V(rev) of I(tail). Cell shrinkage in hyperosmotic solution (400 mmol/kg) increased ECS volume fraction from 0.24 +/- 0.02 to 0.32 +/- 0.02, i.e., by 33%. It had no effect on [K(+)](e) evoked by a depolarizing prepulse in astrocytes, whereas in oligodendrocytes [K(+)](e) rapidly decreased from 52 to 26 mM, i.e., by 50%. The increase in ECS volume was slower than the changes in [K(+)](e). These data demonstrate that hypoosmotic solution has a larger effect on the ECS volume around astrocytes than around oligodendrocytes and that hyperosmotic solution affects the ECS volume around oligodendrocytes only. This indicates that increased K(+) accumulation in the vicinity of oligodendrocytes could be due to a restricted ECS. Oligodendrocytes in the CNS are therefore most likely surrounded by clusters of "compacted" ECS, which may selectively affect the diffusion of neuroactive substances in specific areas and directions and facilitate spatial K(+) buffering.
Keywords: osmolární koncentrace; Neuroglia; Potassium; vodní a elektrolytová rovnováha; Cell Membrane Permeability; Rats; Spinal Cord; Cell Membrane; Organ Culture Techniques; Cell Size; Membrane Potentials; Osmolar Concentration; orgánové kultury - kultivační techniky; oligodendroglie; extracelulární prostor; membránové potenciály; mícha; Electric Stimulation; Potassium Channels; Water-Electrolyte Balance; neuroglie; Animals; osmotický tlak; permeabilita buněčné membrány; zvířata; velikost buňky; Oligodendroglia; Stress, Physiological; fyziologický stres; astrocyty; Astrocytes; krysa rodu Rattus; Osmotic Pressure; buněčná membrána; draslíkové kanály; draslík; elektrická stimulace; Extracellular Space